Improving Writing through Stages - Adriana Maritza Rivera Barreto (Asociación Colombiana de Profesores de Ingles, 2011)
Writing as a means of communication is one of the basic skills students must master at the university level. Although it is not an easy task because students are usually reluctant to correct, teachers have great responsibility at the time of guiding a writing process. For that reason, this study aimed at improving the writing process in fourth semester students from the Engineering Faculty at the Universidad Santo Tomás, Tunja, Colombia, following the writing stages. Data analysis showed that writing improves if students can follow stages and receive feedback from the teacher.